Symmetric modules over their endomorphism rings - Ungor, B.; Kurtulmaz, Y.; Halicioglu, S.; Harmanci, A. (Algebra and Discrete Mathematics, 2015)
Let R be an arbitrary ring with identity and M a right
R-module with S=EndR(M). In this paper, we study right
R-modules M having the property for f,g∈EndR(M) and
for m∈M, the condition fgm=0 implies gfm=0. We prove
that some results of symmetric rings can be extended to symmetric
modules for this general setting.